As aglomerações produtivas de calçados, folheados e de jóias do CRAJUBAR (CE): formação, produção, trabalho, implicações socioespaciais - Cordeiro, Rosemary de Matos [UNESP] (2015)
The overall objective of this thesis is to analyze the general socio-economic and spatial aspects of industrial activity in productive agglomerations of shoes and jewelry plated in Juazeiro, Crato and Barbalha; their productive and recent economic dynamic structures, the intervening factors in its evolution and its current situation, assessing their socio-spatial implications. The nuclear argument is that, given the presence of a set of endogenous factors that characterize the CRAJUBAR, represented by religiosity created around the Padre Cicero figure; for growth, due to population growth, with local market for both religious items as to basic necessities; the appearance on the place of a tacit knowledge, focused on the production of shoes and jewelery diverse, widespread among the sites; by the resulting creation of a historical and cultural tradition founded in the craft/industrial work; a strong entrepreneurship by local actors, can be recognized and emphasized the occurrence and stay until the present day in the CRAJUBAR region, of significant productive agglomerations of footwear and jewelry plated. They appear with sufficient economic dynamism to provide a satisfactory economic expansion to the area, with reasonable offer of employment and income, despite the coexistence of a formal sector and other informal, very significant, allowing the coexistence of two worlds, expressed by the presence of a sector that is modernizing and the continuity and maintenance of archaic production in the two segments studied. The study adopted as methodological approach the literature and field research, being interviewed a total of 95 entrepreneurs in the footwear sector (among formal and informal producers) and 46 productive actors on the jewelry and plated sector (also formal and informal) aside from supporting institutions. Some of the observed results were: existence of productive linkages in both segments derived from the social and technical ...